Divided village - Johnson, Jason B., author.
1 online resource (x, 233 pages)
Keywords: "In 1983, then-US Vice President George H.W. Bush delivered a speech in London. He had just been in West Berlin and spoke about his first visit to the Berlin Wall. Bush then went on to describe another German wall he saw after Berlin: 'If anything, that wall was an even greater obscenity than its eponym to the north.' The story of that wall is a fascinating and valuable slice of the history of post-war Europe. That wall had gone up nearly two hundred miles southwest of Berlin at the edge of divided Germany, in the tiny, remote farming village of Modlareuth. For nearly half the twentieth century, the Iron Curtain divided Modlareuth in two. In this little valley surrounded by forests and fields, the villagers of Modlareuth found themselves on the literal front-line of the Cold War. The East German state gradually militarized the border through the community while eastern villagers exhibited a range of responses to cope with their changing circumstances, reflective of the variable nature of the Cold War border through Germany: along the Iron Curtain, the size and isolation of the divided place influenced the local character of the division"--Provided by publisher.